2022
DOI: 10.1186/s12875-022-01697-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the utilization of community-based health services among older adults in China—an empirical study based on Anderson’s health behavior model

Abstract: Taking the modified Anderson health behavior model as the analysis framework and relying on 1136 empirical research data of S District in Foshan City, Guangdong Province of China, this study explores the influence of predisposing factors, enabling factors and need factors on the utilization of community-based health services among older adults in China. The results show that three variables have a significant impact on the use of family health services, which are whether the pension is the main source of livin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…[ 10 , 11 ]. Furthermore, the utilization of health services has been influenced by age, gender, education, as well as race/ethnicity [ 8 , 12 15 ]. When the different needs of individuals are not taken into account, inequity might happen [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 10 , 11 ]. Furthermore, the utilization of health services has been influenced by age, gender, education, as well as race/ethnicity [ 8 , 12 15 ]. When the different needs of individuals are not taken into account, inequity might happen [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, Andersen's theoretical model is one of the conventionally used models to explain service utilization. Andersen's health service utilization model was developed in western countries and has been extensively tested in various countries [ 15 , 21 , 22 ]. It is a theoretical framework that has been tested by many scholars to explain the determinants of health service use, taking into account individual and societal determinants [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Older people are more likely to experience social isolation due to physical functional limitations that make it difficult for them to participate in social activities, a lack of access to reliable transportation, the burden of greater physical and psychological pain, and the loss of formal social roles and meaningful interpersonal connections. 4 Numerous studies have shown the significant relationship between older people's social networks and health-related quality of life. 5 Individuals who are socially isolated have been proven to have a higher chance of acquiring heart disease, stroke, depression, dementia, and early mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the government should further improve the classification of the older people's health status and economic income evaluation mechanism, formulate detailed and reasonable service subsidy standards, 4 and provide appropriate subsidies for the purchase of health and nursing services for low-income older people who live in economically backward areas or rural areas and do have a demand for health and nursing care services and lack financial capacity. When the financial situation of older people is problematic, they gradually reduce their interaction with the outside world and shrink their social network.…”
mentioning
confidence: 99%